Faith in the living God: a dialogue - Polkinghorne, John C.; Welker, Michael (Cascade Books, 2019)
Introduction / John Polkinghorne and Michael Walker -- pt. 1: Faith in the living God -- Faith in God the creator / John Polkinghorne -- Comments: Is there a natural awareness of God? / Michael Welker -- Reply : Knowledge of God / John Polkinghorne -- Faith in God the creator / Michael Welker -- Comments: Mind and heart / John Polkinghorne -- Reply : "The issue of truth is paramount" / Michael Welker -- Faith in Christ / John Polkinghorne -- Comments: Critical and self-critical realism / Michael Welker -- Reply: Incarnational reality / John Polkinghorne -- Faith in Christ / Michael Welker -- Comments: Witness to the risen Christ / John Polkinghorne -- Reply: "A balance between boldness and careful self-criticism" / Michael Welker -- Faith in the Holy Spirit / John Polkinghorne -- Comments: The working of the Spirit "from below" and "from above" / Michael Welker -- Reply: The personhood of the Spirit / John Polkinghorne -- Faith in the Holy Spirit / Michael Welker -- Comments: Four pneumatological points / John Polkinghorne -- Reply: A sharply phrased protest at the idea of "an abstract omni-presence" / Michael Welker -- pt. 2: 'Faith seeking understanding' in truth-seeking communities and among individuals -- Opening windows onto reality / John Polkinghorne -- Springing cultural traps / Michael Welker -- The search for truth and understanding / John Polkinghorne and Michael Welker.